PERNIKAHAN ANAK USIA DINI DI MEDIA SOSIAL: MUI DALAM SOROTAN PUBLIK (STUDI KASUS KABUPATEN WAJO) - Abd. Haris; Nurfaika (Realism: Law Review, 2024)
This study examines the phenomenon of child marriage in Indonesia, specifically in Wajo Regency, South Sulawesi. The findings reveal that the practice of child marriage remains a serious problem that requires urgent attention from various stakeholders. Collaboration between religious leaders (ulama) and government officials (umara) is key in reducing the prevalence of child marriage. Through various education programs, socialization, and law enforcement, it is hoped that public awareness of the negative impacts of child marriage can be increased. The study found that child marriage not only violates children's rights but also contradicts the objectives of Islamic law. Although marriage aims to establish a harmonious family, early marriage can hinder the achievement of this goal. Children who marry at a young age lack the physical, mental, and emotional maturity required for married life. This research highlights the importance of the roles of government, religious institutions, and the community in preventing and addressing child marriage. Efforts that need to be undertaken include improving the quality of education, providing reproductive health services for adolescents, and strengthening law enforcement against perpetrators of child marriage. It is hoped that these efforts will lead to a decrease in the number of child marriages in Indonesia, particularly in Wajo Regency